Study Of Mothers' Knowledge About Tummy Time Exercise On Infant Motor Development - Nurmaliza Nurmaliza (Jurnal Ilmu Kesehatan Abdurrab, 2024)
ABSTRACT Background Approximately 1-3% of children under the age of 5 years experience developmental delays in gross motor, fine motor, speech and language. Tummy time is one of the recommended stimulations to help gross motor and fine motor development. Tummy time will help develop the brain and body so that it will achieve maximum development. Purpose To determine the study of mothers' knowledge about tummy time exercise on infant motor development. Method Quantitative research using analytic design with a cross sectional approach. This research was conducted in the working area of the Payung Sekaki Health Center and was conducted in November 2023-July 2024. The sample in this study were mothers who had infants aged 0-6 months with a total of 185 respondents using purposive sampling technique. The research instrument was a questionnaire and KPSP sheet. Data analysis technique using univariate and bivariate analysis using chi square test on SPSS 26. Result After carrying out statistical tests using the chi square test obtained (p=0.000), there is a relationship between maternal knowledge about tummy time exercise on motor development (p<0.05). Conclusion A good mother's knowledge encourages mothers to stimulate tummy time in their children, for proper stimulation has a significant effect on children's motor development.